Impact of the expanded old age income security programme on suicide mortality among older adults in South Korea: a quasi-experimental study - Kim, Chungah; Grignon, Michel; Muntaner, Carles; Dunn, James R (Journal of epidemiology and community health (1979), 2025)
This study examined the impact of the expansion, implemented in July 2014, of Korea's tax-financed (non-contributory) old age income security programme, the Basic Pension (BP), on suicide mortality among individuals aged 65+. Using aggregate mortality data from 2010 to 2019, we employed event-history difference-in-differences (DD), 2×2 DD, and difference-in-difference-in-differences (DDD) approaches, leveraging two identification strategies: (1) regional variations in the proportion of BP beneficiaries and (2) a triple-difference strategy incorporating both regional variation and age-based eligibility. Event study models were used to test the common trends assumption and assess the dynamic effects of the reform. The event study findings revealed that the reduction in suicide mortality among older women became more pronounced over time, with significant decreases emerging 10-16 quarters after the reform's implementation. The 2×2 DD analysis reported a 20% (95% CI -33% to -6%) reduction in suicide rates among older women in high-beneficiary regions compared with low-beneficiary regions, and no significant effects were observed for men. The DDD analysis did not yield statistically significant results, but the estimated effect size for women (-17%; 95% CI -52% to 18%) was consistent in direction with the DD analysis. The doubling of social pension benefits in South Korea appears to have contributed to reduced suicide mortality among older women. These findings suggest that targeted income security programmes may help reduce suicide rates among economically vulnerable older adults. They provide valuable insights for low- and middle-income countries considering similar interventions.